L’impératif positif dans les énoncés avec l’adverbe SO - Elisabet Johansson-Manoury (Anglophonia)
This article deals with a particular kind of imperative mood, namely the positive imperative mood in utterances with the adverb SO. Moreover, the verbs which we study are restricted to a specific group including fold, hold, push, tie, and turn. SO refers here to a gesture made by the utterer. This paper aims at showing that the marker SO is linked to the utterer and, more precisely, to the point of view of the utterer.